Stable magnetic fluid anti-icing surfaces supported by a magnetic field and porous substrate. (20th February 2019) - Wang, Ruitong; Hong, Shiquan; Huang, Xiaobin; Liu, Hong
Abstract: The freezing of surfaces in low-temperatures has a significant impact on human productivity and life. To solve this problem, researchers have developed several anti-icing surfaces. Magnetic slippery surfaces have a low ice adhesion strength and high icing delay times. Although the surface magnetic fluid can be bound by a magnetic field, it is still difficult to stably hold the magnetic fluid to the surface. In this paper, we propose an anti-icing system composed of a porous anodic aluminum oxide template and the combination of magnetic fluid and a magnetic field. The anti-icing system maintains a low ice adhesion strength after 70 icing–deicing cycles or a 30 s water jet impact, and the icing delay time is twice that of a superhydrophobic surface. Moreover, the size of the anodic aluminum oxide template can be controlled, and the preparation process is simple. This system can also be applied to a large surface area.